The role of real world data and real world evidence in health technology assessment - E. A. Novoderezhkina; S. К. Zyryanov (Фармакоэкономика)
Real world data (RWD) and real world evidence (RWE) is one of the most rapidly developing areas in the modern health care systems, which is caused by the development of technologies for both collecting and analyzing data, the emergence of new data sources and the formation of needs both by regulatory bodies, health technology assessment (HTA) agencies, and by the clinical and scientific communities. However, at the moment, there is no universal approach to RWD/E generation and application in the context of HTA. Over the past few years, the rate of including RWD/E in the HTA dossier has noticeably increased, but the nature of the existing guidelines and recommendations is rather fragmentary, which might create obstacles in the way of RWD/E study development and submission. The publication is aimed to describe and summarize the main and most rapidly developing spheres of RWD/E applications and analyze the possibilities of using RWD/E in various HTA areas in the world and in the Russian Federation considering the main trends in the further HTA development.